2013
DOI: 10.1155/2013/605854
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model for the Spread of Rumor in Emergencies

Abstract: To study rumor spreading, a novel rumor spreading model with latent, constant recruitment, and varying total population is investigated. We carry out a global qualitative analysis of the rumor spreading model with latent, constant recruitment, and varying total population and studied the existence and stability of the rumor-elimination and prevailing equilibria and the impact different management strategies have on the rumor spreading process. The Runge-Kutta method is used for numerical simulation, and the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As an example of panic behavior, when the Fukushima incident happened after the Tohoku Earthquake on March 11, 2011, it was not the nearby Japanese but the Chinese who lived far away from Fukushima who engaged in panic buying of salt, causing supermarkets in some major cities to run out (Setiogi, 2011). Likewise, drug stores in Russia and British Columbia, Canada (but not Japan), reported shortages of iodine pills, in spite of health officials insisting that potassium iodide is not an antiradiation drug (Chen, Shen, Ye, Chen, & Kerr, 2013). A very relevant case was reported in a news article entitled "A survey showed that opponents of Jiangmen nuclear fuel project were not local residents but entrepreneurs from neighboring cities" (调查称江门反 核者多非当地普通群众 周边城市企业家成急先锋) (Observer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As an example of panic behavior, when the Fukushima incident happened after the Tohoku Earthquake on March 11, 2011, it was not the nearby Japanese but the Chinese who lived far away from Fukushima who engaged in panic buying of salt, causing supermarkets in some major cities to run out (Setiogi, 2011). Likewise, drug stores in Russia and British Columbia, Canada (but not Japan), reported shortages of iodine pills, in spite of health officials insisting that potassium iodide is not an antiradiation drug (Chen, Shen, Ye, Chen, & Kerr, 2013). A very relevant case was reported in a news article entitled "A survey showed that opponents of Jiangmen nuclear fuel project were not local residents but entrepreneurs from neighboring cities" (调查称江门反 核者多非当地普通群众 周边城市企业家成急先锋) (Observer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If β is the incidence coefficient of horizontal transmission, such rate is βS(t)I(t). Besides, some susceptible with profound knowledge (such as experts or scientists in relevant fields) will not be affected by the special public opinion, hence, these people directly recovered at a rate u s , namely natural immunity [27]. And β, u L , u I , u S > 0 Fig.…”
Section: The Simplified Slir Modelmentioning
confidence: 99%
“…Through numerical simulation, it is found that positive actions in the government can improve rumor management in emergencies and generate positive social effects. To study the spread of rumor in emergencies, Chen et al [25] investigated a novel rumor spreading model with latent, constant recruitment, and varying total population. Li et al [26] explored the impact of punishment of governments and sensitivity of individuals on the rumor spreading and then drew a conclusion that improving the punishment of government and increasing the sensitivity of individuals can effectively control the spreading of rumor.…”
Section: Introductionmentioning
confidence: 99%